2020
DOI: 10.1002/jeq2.20153
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the photoinactivation and transport of somatic and F‐specific coliphages at a Great Lakes beach

Abstract: Fecal indicator organisms (FIOs), such as Escherichia coli and enterococci, are often used as surrogates of contamination in the context of beach management; however, bacteriophages may be more reliable indicators than FIO due to their similarity to viral pathogens in terms of size and persistence in the environment. In the past, mechanistic modeling of environmental contamination has focused on FIOs, with virus and bacteriophage modeling efforts remaining limited. In this paper, we describe the development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…For example, Larose et al (2007) concluded that the model is an effective tool for capturing the dynamics of streamflow and atrazine concentrations in a large-scale agricultural watershed in the midwestern United States. Safaie et al (2020) demonstrated that the coliphage F&T model for lakes could be used to test hypotheses about potential sources and their behavior and for predictive modeling. Substantial improvements in watershed-scale models arose from better conceptualization of transport mechanisms, such as for P (Collick et al, 2016;White et al, 2014) and E. coli (Hall et al, 2014;Liao et al, 2015).…”
Section: Modeling In Fandt Researchmentioning
confidence: 99%
“…For example, Larose et al (2007) concluded that the model is an effective tool for capturing the dynamics of streamflow and atrazine concentrations in a large-scale agricultural watershed in the midwestern United States. Safaie et al (2020) demonstrated that the coliphage F&T model for lakes could be used to test hypotheses about potential sources and their behavior and for predictive modeling. Substantial improvements in watershed-scale models arose from better conceptualization of transport mechanisms, such as for P (Collick et al, 2016;White et al, 2014) and E. coli (Hall et al, 2014;Liao et al, 2015).…”
Section: Modeling In Fandt Researchmentioning
confidence: 99%
“…It is imperative to be cognizant of statistical composition of water structure to determine its fit for domestic and industrial usage. Multiple scholarly efforts have been conducted to investigate the quality of water through various numerical, analytical and experimental endeavours 3 , 12 , 14 , 18 , 27 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…To address the impact of regional contamination on beaches, hydrodynamic models have been developed to track contaminant fate and transport to beach areas. Previous research has estimated the transport of contamination from watershed discharges to downstream locations. Rain events have long been understood to contribute pollutants to local waters, with sewer overflows and urban stormwater runoff a known source of pathogens that constitute a risk to human health. Watershed characteristics such as land use are important in evaluating the types of pollutants expected and the potential impacts on nearshore waters, , including potential health risks. Understanding if and when contamination from the greater watershed may reach beaches is necessary to manage water quality impairments and beach advisories.…”
Section: Introductionmentioning
confidence: 99%